A new mixed model of periodontitis‐induced preeclampsia: A pilot study. (8th March 2021) - Mata, Karina; Nobre, Atila Vinícius Vitor; Felix Silva, Pedro Henrique; Oliezer, Rene Seabra; Fernandes, Cleverson; Amaral, Jefferson; Ramos, Junia; Constante Gabriel Del‐Arco, Marina; Messora, Michel Reis; Tanus‐Santos, José Eduardo; Gerlach, Raquel Fernanda; Salvador, Sergio Luiz
Abstract: Objectives/Background: Recent studies have shown that periodontal disease is strongly related to gestational complications such as preeclampsia (PE). PE is responsible for 42% of maternal deaths worldwide and kills approximately 76 000 women a year. In addition, children born under PE conditions are at increased risk of hospitalization due to metabolic disorders, epilepsy, and other complications. Numerous reviews and clinical studies on PE have been published, but the mechanisms underlying the relationship between periodontal disease and PE and the way periodontopathogens alter vascular response in pregnant women remain unclear. Methods: This study aims to verify whether periodontal disease induces PE by using the association of two periodontitis (PD) models: ligature and oral Porphyromonas gingivalis ( P . gingivalis ) W83 inoculation in Wistar rats. At gestational day 5, the ligature was placed on each mandibular first molar, which was followed by daily oral P . gingivalis inoculation for 15 days. At gestational day 19, urine was collected, and invasive arterial pressure was measured. The animals were euthanized, and plasma and tissues were collected. Results: After 15 days of the association of ligature and P . gingivalis inoculation, the animals presented the characteristic symptoms of PE: altered blood pressure, proteinuria, and change in litter size (number of pups) and pup weight when compared to the control group ( p < .005). The PE animals also presented greater bone porosity, trabecular separation, and reduced bone volume in the hemimandibles, as well as altered inflammatory response. The level of cytokine IL‐6 was higher in the PE group than in the control group ( p < .005). Conclusion: The association of two PD models effectively induced PE. To our knowledge, this is the first study on the oral use of P . gingivalis for PE induction. Our results support the importance of PD as a possible cause for PE development, opening an important new avenue to study cause and consequence relationships in inflammation and PE due to exposure to periodontal infection.